Kontribusi Minat Berwirausaha Terhadap Hasil Belajar Kewirausahaan Mahasiswa Pendidikan Vokasi - Budi Syahri; Ganefri Ganefri; Asmar Yulastri (AEEJ : Journal of Automotive Engineering and Vocational Education, 2023)
Seeing the interest of students in entrepreneurship before studying entrepreneurship such as selling online or offline is a study that needs to be done. The existing interest in these students has an influence on students when they take entrepreneurship lessons. This study aims to see how much the contribution of student entrepreneurship interests supports student learning outcomes in entrepreneurship courses. This study uses a type of quantitative research with the nature of correlation research which aims to prove the relationship between variables. Respondents were 35 vocational education students who had become entrepreneurs. The results of the study show a significance value of 0.018 which is less than <0.05 probability so the hypothesis Ha is accepted, that there is an influence between entrepreneurial interest on the entrepreneurship learning outcomes of vocational education students and contributes 15.7%. Melihat adanya minat mahasiswa dalam berwirausaha sebelum mempelajari kewirausahaan seperti berjualan online ataupun offline menjadi sebuah kajian yang perlu dilakukan. Minat yang sudah ada pada mahasiswa tersebut apakah memberikan pengaruh terhadap mahasiswa ketika mereka mengikuti pelajaran kewirausahaan. Penelitian ini bertujuan untuk melihat seberapa besar kontribusi minat berwirausaha mahasiswa untuk menunjang hasil belajar mahasiswa pada mata kuliah kewirausahaan. Penelitian ini menggunakan jenis penelitian kuantitatif dengan sifat penelitian korelasional yang bertujuan untuk membuktikan hubungan antara variabel. Responden sebanyak 35 mahasiswa pendidikan vokasi yang pernah berwirausaha. Hasil penelitian menujukkan nilai signifikansi 0,018 lebih kecil dari < probabilitas 0,05 sehingga hipotesis Ha diterima, bahwa ada pengaruh antara minat berwirausaha terhadap hasil belajar kewirausahaan mahasiswa pendidikan vokasi dan memberikan kontribusi sebesar 15,7%.